Do contractionary monetary policy shocks expand shadow banking?. (31st August 2017) - Nelson, Benjamin; Pinter, Gabor; Theodoridis, Konstantinos
Summary: Using VAR models for the USA, we find that a contractionary monetary policy shock has a persistent negative impact on the level of commercial bank assets, but increases the assets of shadow banks and securitization activity. To explain this "waterbed" effect, we propose a standard New Keynesian model featuring both commercial and shadow banks, and we show that the model comes close to explaining the empirical results. Our findings cast doubt on the idea that monetary policy can usefully "get in all the cracks" of the financial sector in a uniform way.